Association between primary Spanish language and quality of intrapartum care among Latina women: a secondary analysis of the Listening to Mothers in California survey - Jessica J. Valdez; Andrea V. Jackson; Cassondra Marshall (BMC, 2023)
Abstract Background Language barriers play significant roles in quality of healthcare. Limited studies have examined the relationships between Spanish language and quality of intrapartum care. The objective was to determine the association between primary Spanish language and quality of intrapartum care so as to further inform best practices for non-English speaking patients in the labor and delivery setting. Methods We used the 2016 Listening to Mothers in California survey data, which included a statewide representative sample of women who gave birth in hospitals. Our analytical sample included 1202 Latina women. Multivariable logistic regression was used to examine the association between primary language (monolingual English vs. monolingual Spanish vs. bilingual Spanish/English) and perceived discrimination due to language, perceived pressure for medical interventions, and mistreatment during labor, adjusting for maternal sociodemographics and other maternal and neonatal factors. Results Over one-third of the study population spoke English (35.6%), less than one-third spoke Spanish (29.1%), and greater than one-third spoke bilingual Spanish/English (35.3%). Overall, 5.4% of Latina women perceived discrimination due to language spoken, 23.1% perceived pressure for any medical intervention, and 10.1% experienced either form of mistreatment. Compared to English-speakers, Spanish-speakers were significantly more likely to report discrimination due to language (aOR 4.36; 95% CI 1.15-16.59), but were significantly less likely to experience pressure for certain medical interventions (labor induction or cesarean delivery) during labor (aOR 0.34; 95% CI 0.15-0.79 for induction; aOR 0.44; 95% CI 0.18-0.97 for cesarean delivery). Bilingual Spanish/English-speakers also significantly reported discrimination due to language to a lesser extent than monolingual Spanish-speakers (aOR 3.37; 95% CI 1.12-10.13). Any form of Spanish language (monolingual or bilingual) was not significantly associated with mistreatment. Conclusions Spanish language may contribute to experiences of discrimination during intrapartum care among Latina women. Future research is needed to explore perceptions of pressure, discrimination and mistreatment, among patients with limited English proficiency.